THE USE OF SIMPLEMIND APP IN TEACHING READING - Utami Kusuma Ningtyas (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2015)
Abstract: It has been known that reading achievement influences academic and professional success. Unfortunately, Indonesian students are still categorized as struggle readers. Reading strategy and reading engagement has to be a part of reading instruction. In addition, the presence of technology in teaching reading cannot be taken for granted. Students nowadays are digital native who are surrounded with technology. SimpleMind App is the collaboration between mind-mapping as and technology. This paper reviews the importance of reading strategy and reading engagement, the role of technology in teaching reading, and the procedures of teaching reading with SimpleMind App.Keywords: reading achievement, teaching reading, SimpleMind App